2018
DOI: 10.1111/gcbb.12568
|View full text |Cite
|
Sign up to set email alerts
|

How is biodiversity protection influencing the potential for bioenergy feedstock production on grasslands?

Abstract: Sustainable feedstock supply is a critical issue for the bioenergy sector. One concern is that feedstock production will impact biodiversity. We analyze how this concern is addressed in assessments of biomass supply potentials and in selected governance systems in the EU and Brazil, including the EU Renewable Energy Directive (RED), the EU Common Agricultural Policy (CAP), and the Brazilian Forest Act. The analysis focuses on grasslands and includes estimates of the amount of grassland area (and corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The Drax power station is the largest in the UK based on its power output and has converted four of its six power generators to use wood pellets as a feedstock (Drax, 2018). The use of biomass to meet such a large demand for energy can create issues with sustainable land use, water supply (Schyns and Vanham, 2019), and the protection of biodiversity (Fingerman et al, 2019, Hansson et al, 2019. The direct and indirect implications of land and crop management such as the carbon stock that is maintained in the soil must be considered and acted upon appropriately over relevant time periods, which can take decades to replenish for forestry products (Searchinger et al, 2018).…”
Section: Fertilisermentioning
confidence: 99%
“…The Drax power station is the largest in the UK based on its power output and has converted four of its six power generators to use wood pellets as a feedstock (Drax, 2018). The use of biomass to meet such a large demand for energy can create issues with sustainable land use, water supply (Schyns and Vanham, 2019), and the protection of biodiversity (Fingerman et al, 2019, Hansson et al, 2019. The direct and indirect implications of land and crop management such as the carbon stock that is maintained in the soil must be considered and acted upon appropriately over relevant time periods, which can take decades to replenish for forestry products (Searchinger et al, 2018).…”
Section: Fertilisermentioning
confidence: 99%
“…The productivity developments in the livestock sector, and particularly grasslands, are Land 2020, 9, 457 2 of 18 not yet properly assessed and are not included in existing modeling frameworks [14,15] despite the vast amount of grassland used for livestock production [16]. While Ketzer et al [17], Qi et al [18] and Hansson et al [19] have shown substantial land and bioenergy potential of grasslands in parts of Europe, they did not consider the integral environmental impacts of intensification in the livestock sector as a means to allow additional biomass for energy or other purposes. Gerssen-Gondelach et al [8] did account for livestock productivity intensification in their assessment of bioenergy potential through intensification and integral emission analysis, but they only included increased livestock stocking rates.…”
Section: Introductionmentioning
confidence: 99%